Effect of tooth bleaching agents on protein content and mechanical properties of dental enamel. (1st July 2015) - Elfallah, Hunida M.; Bertassoni, Luiz E.; Charadram, Nattida; Rathsam, Catherine; Swain, Michael V.
Graphical abstract: Abstract: This study investigated the effect of two bleaching agents, 16% carbamide peroxide (CP) and 35% hydrogen peroxide (HP), on the mechanical properties and protein content of human enamel from freshly extracted teeth. The protein components of control and treated enamel were extracted and examined on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS–PAGE). Marked reduction of the protein matrix and random fragmentation of the enamel proteins after bleaching treatments was found. The mechanical properties were analyzed with Vickers indentations to characterize fracture toughness, and nanoindentation to establish enamel hardness, elastic modulus and creep deformation. Results indicate that the hardness and elastic modulus of enamel were significantly reduced after treatment with CP and HP. After bleaching, the creep deformation at maximum load increased and the recovery upon unloading reduced. Crack lengths of CP and HP treated enamel were increased, while fracture toughness decreased. Additionally, the microstructures of fractured and indented samples were examined with field emission gun scanning electron microscopy (FEG-SEM) showing distinct differences in the fracture surface morphology between pre- and post-bleached enamel. In conclusion, tooth bleaching agents can produce detrimental effects on the mechanical properties of enamel, possibly as a consequence of damaging or denaturing of its protein components.